2005
DOI: 10.1091/mbc.e04-10-0926
|View full text |Cite
|
Sign up to set email alerts
|

TheXenopusTACC Homologue, Maskin, Functions in Mitotic Spindle Assembly

Abstract: Maskin is the Xenopus homolog of the transforming acidic coiled coil (TACC)-family of microtubule and centrosomeinteracting proteins. Members of this family share a ϳ200 amino acid coiled coil motif at their C-termini, but have only limited homology outside of this domain. In all species examined thus far, perturbations of TACC proteins lead to disruptions of cell cycle progression and/or embryonic lethality. In Drosophila, Caenorhabditis elegans, and humans, these disruptions have been attributed to mitotic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
86
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(92 citation statements)
references
References 59 publications
5
86
0
1
Order By: Relevance
“…Moreover, eIF4A, a component of eIF4F, similarly failed to efficiently co-precipitate with CPEB, attesting to the specificity of the interactions described above. We also probed with antibodies raised against Xenopus maskin (TACC3), obtained from three laboratories (15,51,52), and the deadenylase PARN (53) but did not observe significant binding (Fig. 1G) (see "Discussion").…”
Section: Characterization Of the Cpeb Rnp Complex In Xenopusmentioning
confidence: 98%
“…Moreover, eIF4A, a component of eIF4F, similarly failed to efficiently co-precipitate with CPEB, attesting to the specificity of the interactions described above. We also probed with antibodies raised against Xenopus maskin (TACC3), obtained from three laboratories (15,51,52), and the deadenylase PARN (53) but did not observe significant binding (Fig. 1G) (see "Discussion").…”
Section: Characterization Of the Cpeb Rnp Complex In Xenopusmentioning
confidence: 98%
“…CPE binds CPEB. In Xenopus, CPEB binds maskin, which in turn binds XMAP215, the homolog of TOG; TACC, the maskin homolog, also binds TOG (Conte et al, 2003;O'Brien et al, 2005); it is not clear, however, that TACC is functionally similar to maskin with regard to translation. The CPEB-maskin complex is known to inhibit translation of CPE-containing mRNAs in neurons (Huang and Richter, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…TACC1 has been identified as a TOG binding partner in a yeast two-hybrid screen (Lauffart et al, 2002). However, there is no reported interaction between TACC1 and CPEB, and TOG has not been implicated previously in translational regulation (Conte et al, 2003;O'Brien et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…O'Brien et al 5 found that Maskin interacts with XMAP215 in a manner that seems similar to how other TACC proteins act: although XMAP215 can bind to microtubules in Maskin-depleted egg extracts, it fails to accumulate at spindle poles. The Maskin-depleted extracts form undersized asters in response to Ran-GTP and assemble highly disorganized spindles around added sperm chromosomes.…”
mentioning
confidence: 95%
“…One possible mechanism is suggested by another recent study by O'Brien et al 5 , who investigated the role of Maskin in spindle assembly. Maskin is a member of the 'transforming acidic coiled coil' (TACC) protein family, and is the first TACC protein to have been found in Xenopus 6 .…”
mentioning
confidence: 98%